2020
DOI: 10.4236/jhepgc.2020.64045
|View full text |Cite
|
Sign up to set email alerts
|

The Essence and Origin of the Magnetic Constant

Abstract: In this study, the essence and origin of the magnetic constant are discussed and a mechanism that allows real estimations of the magnetic constant based upon the vacuum density description is proposed. By considering the vacuum as a liquid with a measurable density and the electron as a vortex, hydrodynamic laws are applied to measure the diminished momentum of a rotating electron in a vacuum, thus obtaining a value similar to the experimentally derived value of the magnetic constant. A consequence of this des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In a previous study [37], we demonstrated that the electric permittivity constant represents the elasticity of the vacuum, which exhibits the value of 8.87337441 × 10 −12 kgcm/s 2 cm 3 or 8.87337441 × 10 −10 kgm/s 2 m 2 ; thus, the photon density can be calculated as follows: where c 2 = 9 × 10 16 m 2 /s 2 , which is the same value of the vacuum density [38].…”
Section: The Rest Mass and Density Of Photonmentioning
confidence: 87%
See 1 more Smart Citation
“…In a previous study [37], we demonstrated that the electric permittivity constant represents the elasticity of the vacuum, which exhibits the value of 8.87337441 × 10 −12 kgcm/s 2 cm 3 or 8.87337441 × 10 −10 kgm/s 2 m 2 ; thus, the photon density can be calculated as follows: where c 2 = 9 × 10 16 m 2 /s 2 , which is the same value of the vacuum density [38].…”
Section: The Rest Mass and Density Of Photonmentioning
confidence: 87%
“…where ρ v denotes the vacuum density, u denotes the angular velocity, and λ denotes the vortex perimeter [38].…”
Section: N Buttomentioning
confidence: 99%
“…with 𝞺 resistivity of copper is 1.68 × 10 -8 ohm-m, μ0 magnetic permeability of vacuum is 12.57×10 -7 H/m [36], [37]. If the values of those constants are used and the frequency of the RF is 77.77 MHz, then it is obtained that: The resistance calculation in the dee and the stem.…”
Section: The Second Methodsmentioning
confidence: 99%
“…In a previous study [20], the vacuum density was discussed in detail. The best estimate of the cosmological density was between 9.75839983 × 10 −27 and (11.11 ±1.05) × 10 −27 kg/m 3 .…”
Section: N Buttomentioning
confidence: 99%